A boroaluminate glass-ceramic with controllable crystallization and its preparation method and application
By using nanooxides as induced seed crystals in boron aluminate glass, the precise and controllable precipitation of crystal phases in microcrystalline glass is achieved, and the coloring problems caused by the difficulty of crystal phase control in the prior art and TiO2 are solved, and microcrystalline glass with high hardness, crack resistance and high transparency are prepared.
Patent Information
- Application Number
- CN202310063710.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-06
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2043-02-06
AI Technical Summary
It is difficult to achieve accurate control of the size, morphology, type, distribution and content of existing boron aluminate glass during microcrystalization, which makes it difficult to prepare transparent optical microcrystalline glass, and TiO2 as a crystal nucleation agent will cause glass coloring, limiting its application.
Nanooxides are used as the induced seed crystals, and nanooxides are added after the glass is formed. By controlling the size, morphology, type, distribution and content of the nanooxides, the precise and controllable precipitation of the crystal phases in the microcrystalline glass is achieved.
The controllable precipitation of the crystal phase in the microcrystalline glass is realized, which improves the hardness and crack resistance of the glass, while maintaining high transparency, and is suitable for display cover glass for portable electronic devices.
Smart Images

Figure CN115872623B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of glass-ceramics, and in particular to a boroaluminate glass-ceramics with controllable crystallization, a preparation method and application thereof. Background Art
[0002] Cover glass is an important component of modern smart terminal portable devices, and it plays an important role in protecting display devices from external damage. The widely used cover glass at present is mainly a high-alumina-silicon glass system. Although this glass can further improve its drop resistance through chemical strengthening methods, the sum of the content of aluminum oxide and silicon oxide in its composition is close to or exceeds 80wt%, which makes its high-temperature melting (>1600℃) and molding very difficult, and the corresponding preparation cost is relatively high. Boroaluminate glass is a new type of glass that does not contain SiO2 and is mainly composed of B2O3 and Al2O3. Compared with high-alumina-silicon glass, boroaluminate glass has a higher content of B2O3 (≥50wt%), which makes its melting temperature lower and easier to mold. At the same time, this glass has also been found to have excellent crack propagation resistance, but its low hardness limits its further expansion of application in cover glass.
[0003] Microcrystallization is one of the effective means to improve the hardness of glass. Therefore, microcrystallization of boroaluminate glass can improve the hardness of glass without changing the glass formula and further increasing the difficulty of the process. However, TiO2 must often be added as a nucleating agent in the microcrystallization of boroaluminate glass, but TiO2 will make the glass yellow-brown, which limits its further application in the field of cover glass. In addition, for cover glass or transparent optical microcrystal glass, high transmittance to visible light is one of the prerequisites that must be met for its use. The microcrystallization of traditional boroaluminate glass is mainly completed by regulating the basic glass components and optimizing the multi-stage heat treatment crystallization system. The nucleating agent is directly added to the glass composition and formed into the basic glass through a high-temperature melting. In this process, the structure of the nucleating agent is easily destroyed by high-temperature melting, and it participates in the formation of the glass network structure. Its disadvantage is that although the nucleating agent improves the crystallization ability of the basic glass, it generally provides nucleation sites during the crystallization process of the crystallization stage, and it is difficult to effectively control the size, morphology, type, distribution and content of the precipitated crystal phase. It is difficult to achieve precise and controllable precipitation of the nanocrystalline phase in the glass only by promoting crystallization with the nucleating agent, which makes the preparation of transparent optical microcrystalline glass difficult to achieve. Since the transmittance of microcrystalline glass is generally closely related to the state of the crystal phase, if the crystal phase size is too large (>800nm), the transmittance of the microcrystalline glass will decrease rapidly or even become devitrified. Therefore, it is challenging to prepare a high-transmittance and high-strength microcrystalline glass cover material while avoiding the TiO2 coloring effect.
[0004] To this end, the present invention proposes a boroaluminate glass-ceramic with controllable crystallization, a preparation method and an application thereof. Summary of the invention
[0005] In order to solve the above-mentioned deficiencies in the prior art, the present invention provides a boroaluminate glass-ceramic with controllable crystallization, and a preparation method and application thereof.
[0006] The boroaluminate glass-ceramics with controllable crystallization and its preparation method and application are realized by the following technical solutions:
[0007] A method for preparing boroaluminate glass-ceramics with controllable crystallization comprises the following steps:
[0008] S1. According to the following mass percentage ratios, weigh the corresponding raw materials for preparing the basic glass respectively, mix them evenly, and obtain a mixed powder for standby use:
[0009] Li2O 9%-16%, Al2O3 25%-42%, B2O3 35%-55%, P2O 50%-3%, ZrO2 0-3%, and the total amount of Li2O, Al2O3, B2O3, P2O5 and ZrO2 is 100%;
[0010] S2, subjecting the mixed powder to a first smelting treatment until it is molten to obtain a glass melt A; cooling the glass melt A to room temperature, and then grinding it to obtain a basic glass powder;
[0011] S3, using nano-oxide as an induction seed, mixing it with the basic glass powder evenly, and then subjecting it to a second smelting treatment until it is in a molten state, to obtain a glass melt B;
[0012] S4. The glass melt B is cast into a shape by a casting method, and after annealing, a boroaluminate glass-ceramics A is obtained.
[0013] Furthermore, the method further includes S5, crystallizing the boroaluminate glass-ceramics A at a temperature of 650-750° C. to obtain boroaluminate glass-ceramics B.
[0014] Furthermore, the crystallization treatment time is 2 to 8 hours.
[0015] Further, the nano-oxide is one or more of Al2O3, SiO2, ZnO, ZrO2, Y2O3, MgO and CaO;
[0016] The usage ratio of the nano oxide to the basic glass powder is 1:15-25.
[0017] Furthermore, in S2, the glass melt A is cooled to room temperature at a cooling rate of 10 to 60°C / s.
[0018] Furthermore, the nano-oxide is added in any one of the states of particles, plates and needles; and the particle size of the nano-oxide is 5 to 20 nm.
[0019] Furthermore, the smelting temperature of the first smelting treatment is 1350-1500° C., and the smelting time is 2-8 hours.
[0020] Furthermore, the smelting temperature of the second smelting treatment is 1350-1500° C., and the smelting time is 2-4 hours.
[0021] The second object of the present invention is to provide a boroaluminate glass-ceramics prepared by the above preparation method.
[0022] The third object of the present invention is to provide an application of the above-mentioned boroaluminate glass-ceramics in the preparation of display cover glass and transparent optical glass-ceramics for portable electronic devices.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] The present invention uses nano-oxide as an inducing crystal seed, which can greatly improve the crystallization ability of boroaluminate glass. In addition, the present invention further plays an inducing crystallization role of the crystal phase by adding nano-oxide of nano-crystalline phase after the glass is formed. By controlling the size, morphology, type, content and distribution of the added nano-crystalline phase, the purpose of accurately controlling the size, morphology, type, content and distribution of the crystal phase precipitated in the micro-ceramic glass is achieved, so that the precipitation of the crystal phase in the micro-ceramic glass presents a controllable situation, which is conducive to the controllable precipitation of the nano-crystalline phase in the micro-ceramic glass, thereby achieving the purpose of strengthening the micro-ceramic glass without reducing the visible light transmittance of the base glass. The controllable precipitation of the micro-crystalline phase can not only greatly improve the surface hardness of the base glass, but also effectively prevent the further expansion of cracks on the surface of the glass, and prevent the glass from cracking over a large area. The hardness value of the prepared microcrystalline glass is 6.0~9.0GPa, and the size of the crystal phase precipitated in the microcrystalline glass is 15~40nm. Its absorption and scattering effects on visible light are small. Therefore, the prepared microcrystalline glass has a transmittance of >90% in the visible light band (400~800nm), and has good application prospects in the field of display cover glass for portable electronic devices.
[0025] The microcrystalline glass prepared by the present invention has the characteristics of low melting temperature, simple molding, convenience for ion exchange strengthening, high strength and high transparency. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is the XRD spectrum of the glass-ceramics described in Example 1. DETAILED DESCRIPTION
[0027] As described in the background technology, the present invention takes into account that the traditional nucleating agent is mainly added simultaneously with other raw material components when preparing glass, and the glass is formed by in-situ crystallization. However, this method often has the disadvantages that the crystallization degree is difficult to control, such as large size of precipitated crystal phase, difficult to grasp the content of crystal phase, uncontrollable morphology of precipitated phase, and difficult to determine the distribution of precipitated phase. For this reason, the present invention uses nano-oxide as an inducing crystal seed and adds it after the glass is formed, which can not only further play the role of inducing crystallization of the crystal phase, but also can achieve the purpose of precise control of the size, morphology, type, content and distribution of the precipitated crystal phase in the microcrystalline glass by controlling the size, morphology, type, content and distribution of the added nano-crystalline phase, so that the precipitation of the crystal phase in the microcrystalline glass presents a controllable situation, which is conducive to the controllable precipitation of the nano-crystalline phase in the microcrystalline glass, so as to achieve the purpose of strengthening the microcrystalline glass without reducing the visible light transmittance of the base glass. And the technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiment of the present invention.
[0028] The present invention provides a boroaluminate glass-ceramic, and the preparation method thereof is as follows:
[0029] S1. According to the following mass percentage ratios, weigh the corresponding raw materials for preparing the basic glass respectively, mix them evenly, and obtain a mixed powder for standby use:
[0030] Li2O 9%~16%, Al2O3 25%~42%, B2O3 35%~55%, P2O 50%~3%, ZrO2 0~3%, and the total amount of Li2O, Al2O3, B2O3, P2O5 and ZrO2 is 100%;
[0031] It should be noted that the present invention does not limit the mixing method of the various raw materials, as long as they can be fully mixed, such as by ball milling or mechanical grinding.
[0032] S2, subjecting the mixed powder to a first smelting treatment until it is molten to obtain a glass melt A; rapidly cooling the glass melt A to room temperature, and then grinding the mixed powder to obtain a basic glass powder;
[0033] It should be noted that the present invention takes into account the specific composition range of the glass. In order to ensure the complete melting and sufficient homogenization of the mixed powder, the mixed powder is melted to a molten state at a temperature of 1350-1500°C, and the present invention does not limit the specific melting time. The treatment is carried out for a corresponding time according to the specifically selected temperature. As long as the mixed powder can be melted to a molten state and each component forms a glass melt A with uniform composition, it can be sufficient, for example, keeping it warm at a temperature of 1350-1500°C for 2-8 hours.
[0034] The present invention forms amorphous glass by rapidly cooling the glass melt A. In order to ensure that the glass melt A can form a glass body, the glass melt A is preferably cooled to room temperature at a cooling rate of 10 to 60° C. / s.
[0035] The present invention does not limit the specific process of the grinding treatment, as long as it can be ground to obtain a basic glass powder with a particle size of 10 to 30 μm.
[0036] S3, using nano-oxide as an induction seed, mixing it with the basic glass powder evenly, and then subjecting it to a second smelting treatment until it is in a molten state, to obtain a glass melt B;
[0037] It should be noted that the present invention does not limit the specific composition of nano oxides. The selected nano oxides can be selected as long as they do not cause glass coloring. For example, they can be selected from one or more of Al2O3, SiO2, ZnO, ZrO2, Y2O3, MgO and CaO. The present invention uses nano oxides of nano crystal phase as induced crystal seeds, which are added after the base glass is formed, and then smelted to allow the nano oxides to fully exert their induced crystallization effect, so that the size, morphology, content and distribution of the crystal phase precipitated in the base glass are all affected by the corresponding size, morphology, content and distribution of the induced crystal seeds themselves. Therefore, the precipitation of the crystal phase in the microcrystalline glass presents a controllable precipitation trend, which is conducive to the controllable precipitation of the nano crystal phase in the microcrystalline glass, thereby achieving the purpose of strengthening the microcrystalline glass without reducing the visible light transmittance of the base glass. The controllable microcrystalline phase precipitation can not only greatly improve the surface hardness of the base glass, but also effectively organize the further expansion of cracks on the surface of the glass, and prevent the glass from cracking over a large area. Therefore, the particle size of the nano oxide preferably used in the present invention is 5 to 20 nm.
[0038] The present invention preferably uses a wet mixing method to mix the nano oxide and the basic glass powder uniformly. The present invention does not limit the specific mixing process, as long as the nano oxide and the basic glass powder can be fully mixed. For example, the following method can be used: ethanol is used as the medium solution, the ratio of ball: material: ethanol is 1:1:1, and the mixing is 10 hours. And because there will be residual medium solution in the material after wet mixing, it is necessary to perform a drying process before the second smelting process to remove the residual medium solvent.
[0039] S4, casting the glass melt B into a shape by a casting method, and performing annealing treatment to obtain boroaluminate glass-ceramics A;
[0040] It should be noted that, based on the glass composition and thermodynamic properties of the present invention, the preferred glass melt B is annealed at a temperature of 400-600°C after being cast to slowly release and eliminate the thermal stress generated by the glass during the casting process, thereby ensuring that the glass does not explode after being formed.
[0041] In order to improve the overall strength of the glass, the present invention can also perform a crystallization treatment on the boroaluminate glass-ceramics A at a temperature of 650-750° C. to obtain a boroaluminate glass-ceramics B. Through the crystallization treatment, the boroaluminate glass-ceramics A is further deeply crystallized, and nano-oxides are added as inducing crystal seeds to improve the crystallization ability of the glass and the precipitation rate of nano-crystals in the entire glass, thereby improving the overall strength of the glass.
[0042] Example 1
[0043] This embodiment provides a boroaluminate glass-ceramic, and the preparation method thereof is as follows:
[0044] Step 1: According to the weight ratio of the following oxides: Li2O (13%), Al2O3 (30%), B2O3 (53%), P2O5 (2%), ZrO2 (2%), accurately weigh and mix them evenly for later use;
[0045] Step 2: Melt the uniformly mixed raw materials in a high-temperature furnace at 1450° C. for 4 hours to obtain a uniform glass melt, and then quickly cool it to obtain a base glass, and then grind the base glass to 10-30 μm for later use;
[0046] Step 3, wet-mixing needle-shaped ZnO with a particle size of 5 to 20 nm and basic glass powder in a mass ratio of 1:25, mixing evenly and drying for later use;
[0047] Step 4: Place the dried mixed powder in step 3 into a high-temperature furnace for melting at a melting temperature of 1250° C. and a heat preservation time of 1 hour to obtain a uniform glass melt.
[0048] Step 5: Use a casting method to quickly shape the obtained glass melt, put it into an annealing furnace for annealing to eliminate thermal stress. The annealing furnace is set at a temperature of 520° C. and the annealing holding time is 2 hours to obtain boroaluminate microcrystalline glass.
[0049] Example 2
[0050] This embodiment provides a boroaluminate glass-ceramic, and the preparation method thereof is as follows:
[0051] Step 1: According to the weight ratio of the following oxides: Li2O (9%), Al2O3 (42%), B2O3 (46%), ZrO2 (3%), weigh them accurately, mix them evenly and set aside;
[0052] Step 2: Melt the uniformly mixed raw materials in a high-temperature furnace at 1500° C. for 6 hours to obtain a uniform glass melt, and then quickly cool the melt to obtain a base glass, which is then ground to 10 to 30 μm for later use;
[0053] Step 3: wet-mix granular SiO2 with a particle size of 5 to 20 nm, plate-shaped Y2O3 with a particle size of 5 to 50 nm, and basic glass powder in a mass ratio of 1:1:30, mix well, and then dry for later use;
[0054] Step 4: Place the dried mixed powder in step 3 into a high-temperature furnace for melting at a melting temperature of 1350° C. and a heat preservation time of 2.0 h to obtain a uniform glass melt.
[0055] Step 5: Use a casting method to quickly shape the obtained glass melt, put it into an annealing furnace for annealing to eliminate thermal stress. The annealing furnace is set at a temperature of 600° C. and the annealing holding time is 4 hours to obtain boroaluminate microcrystalline glass.
[0056] Example 3
[0057] This embodiment provides a boroaluminate glass-ceramic, and the preparation method thereof is as follows:
[0058] Step 1: According to the weight ratio of the following oxides: Li2O (14%), Al2O3 (25%), B2O3 (55%), P2O5 (3%), ZrO2 (3%), accurately weigh and mix them evenly for later use;
[0059] Step 2: Melt the uniformly mixed raw materials in a high-temperature furnace at 1350° C. for 8 hours to obtain a uniform glass melt, and then quickly cool it to obtain a base glass, and then grind the base glass to 10-30 μm for later use;
[0060] Step 3, wet-mixing granular ZrO2 with a particle size of 5 to 20 nm, granular Al2O3 with a particle size of 5 to 100 nm and basic glass powder in a mass ratio of 1:1:35, mixing evenly and drying for later use;
[0061] Step 4: Place the dried mixed powder in step 3 into a high-temperature furnace for melting at a melting temperature of 1100° C. and a heat preservation time of 1 hour to obtain a uniform glass melt.
[0062] Step 5: Use a casting method to quickly shape the obtained glass melt, put it into an annealing furnace for annealing to eliminate thermal stress. The annealing furnace is set at a temperature of 400° C. and the annealing holding time is 3 hours to obtain boroaluminate microcrystalline glass.
[0063] Step six: Place the above-mentioned boroaluminate glass-ceramics in a high-temperature furnace for crystallization heat treatment. The crystallization temperature is set to 650° C. and the crystallization time is 3 hours. Then, cool the furnace to obtain glass-ceramics with enhanced performance.
[0064] Example 4
[0065] This embodiment provides a boroaluminate glass-ceramic, and the preparation method thereof is as follows:
[0066] Step 1: According to the weight ratio of the following oxides: Li2O (16%), Al2O3 (32%), B2O3 (50%), P2O5 (2%), accurately weigh and mix them evenly for later use;
[0067] Step 2: Melt the uniformly mixed raw materials in a high-temperature furnace at 1500° C. for 6 hours to obtain a uniform glass melt, and then quickly cool the melt to obtain a base glass, which is then ground to 10 to 30 μm for later use;
[0068] Step 3: Wet-mix granular CaO with a particle size of 5 to 20 nm and basic glass powder in a mass ratio of 1:22, mix well and then dry for later use;
[0069] Step 4: Place the dried mixed powder in step 3 into a high-temperature furnace for melting at a melting temperature of 1300° C. and a heat preservation time of 1.0 h to obtain a uniform glass melt.
[0070] Step 5: Use a casting method to quickly shape the obtained glass melt, put it into an annealing furnace for annealing to eliminate thermal stress. The annealing furnace is set at a temperature of 525° C. and the annealing holding time is 3 hours to obtain boroaluminate glass-ceramics.
[0071] Example 5
[0072] This embodiment provides a boroaluminate glass-ceramic, and the preparation method thereof is as follows:
[0073] Step 1: According to the weight ratio of the following oxides: Li2O (12%), Al2O3 (32%), B2O3 (52%), P2O5 (2%), ZrO2 (2%), accurately weigh and mix them evenly for later use;
[0074] Step 2: Melt the uniformly mixed raw materials in a high-temperature furnace at 1480°C for 2 hours to obtain a uniform glass melt, and then quickly cool the melt to obtain a base glass, which is then ground to 10-30 μm for later use;
[0075] Step 3, wet-mixing granular Al2O3, SiO2, MgO, CaO with a particle size of 5 to 20 nm with basic glass powder in a mass ratio of 1:1:1:1:85, mixing evenly and drying for later use;
[0076] Step 4: Place the dried mixed powder in step 3 into a high-temperature furnace for melting at a melting temperature of 1280° C. for a holding time of 0.5 h to obtain a uniform glass melt.
[0077] Step 5: Use a casting method to quickly shape the obtained glass melt, put it into an annealing furnace for annealing to eliminate thermal stress. The annealing furnace is set at a temperature of 520° C. and the annealing holding time is 2 hours to obtain boroaluminate microcrystalline glass.
[0078] Step 6: Place the above-mentioned boroaluminate glass-ceramics in a high-temperature furnace for crystallization heat treatment. The crystallization temperature is set to 660° C. and the crystallization time is 2 hours. Then, the glass-ceramics with enhanced performance are obtained by cooling the furnace.
[0079] Example 6
[0080] This embodiment provides a boroaluminate glass-ceramic, and the preparation method thereof is as follows:
[0081] Step 1: According to the weight ratio of the following oxides: Li2O (16%), Al2O3 (28%), B2O3 (53%), P2O5 (1%), ZrO2 (2%), accurately weigh and mix them evenly for later use;
[0082] Step 2: Melt the uniformly mixed raw materials in a high-temperature furnace at 1460° C. for 2 hours to obtain a uniform glass melt, and then quickly cool the melt to obtain a base glass, which is then ground to 10 to 30 μm for later use;
[0083] Step 3, wet-mix granular ZrO2, SiO2, Y2O3 with a particle size of 5 to 20 nm with basic glass powder in a mass ratio of 1:1:1:60, mix well and dry for later use;
[0084] Step 4: Place the dried mixed powder in step 3 into a high-temperature furnace for melting at a melting temperature of 1260° C. for 1.5 h to obtain a uniform glass melt.
[0085] Step 5: Use a casting method to quickly shape the obtained glass melt, put it into an annealing furnace for annealing to eliminate thermal stress. The annealing furnace is set at a temperature of 560° C. and the annealing holding time is 2 hours to obtain boroaluminate microcrystalline glass.
[0086] Step six: Place the above-mentioned boroaluminate glass-ceramics in a high-temperature furnace for crystallization heat treatment. The crystallization temperature is set to 750° C. and the crystallization time is 3 hours. Then, the glass-ceramics with enhanced performance are obtained by cooling the furnace.
[0087] Example 7
[0088] This embodiment provides a boroaluminate glass-ceramic, and the preparation method thereof is as follows:
[0089] Step 1: According to the weight ratio of the following oxides: Li2O (10%), Al2O3 (40%), B2O3 (48%), P2O5 (1%), ZrO2 (1%), accurately weigh and mix them evenly for later use;
[0090] Step 2: Melt the uniformly mixed raw materials in a high-temperature furnace at 1480°C for 5 hours to obtain a uniform glass melt, and then quickly cool it to obtain a base glass, and then grind the base glass to 10-30 μm for later use;
[0091] Step 3: Wet-mix granular Y2O3 with a particle size of 5 to 20 nm with basic glass powder in a mass ratio of 1:23, mix well and dry for later use;
[0092] Step 4: Place the dried mixed powder in step 3 into a high-temperature furnace for melting at a melting temperature of 1300° C. for 1.5 h to obtain a uniform glass melt.
[0093] Step 5: Use a casting method to quickly shape the obtained glass melt, put it into an annealing furnace for annealing to eliminate thermal stress. The annealing furnace is set at a temperature of 550° C. and the annealing holding time is 2 hours to obtain boroaluminate microcrystalline glass.
[0094] Step six: Place the boroaluminate glass-ceramics in a high-temperature furnace for crystallization heat treatment. The crystallization temperature is set to 650° C. and the crystallization time is 8 hours. Then, the glass-ceramics with enhanced performance is obtained by cooling the furnace.
[0095] Example 8
[0096] This embodiment provides a boroaluminate glass-ceramic, and the preparation method thereof is as follows:
[0097] Step 1: According to the weight ratio of the following oxides: Li2O (11%), Al2O3 (38%), B2O3 (49%), P2O5 (1%), ZrO2 (1%), accurately weigh and mix them evenly for later use;
[0098] Step 2: Melt the uniformly mixed raw materials in a high-temperature furnace at 1480°C for 3 hours to obtain a uniform glass melt, and quickly cool it to obtain a base glass, and then grind the base glass to 10-30 μm for later use;
[0099] Step 3, wet-mixing SiO2 and ZnO granules with a particle size of 5 to 20 nm with basic glass powder in a mass ratio of 1:1:47, mixing evenly and drying for later use;
[0100] Step 4: Place the dried mixed powder in step 3 into a high-temperature furnace for melting at a melting temperature of 1300° C. for a holding time of 0.5 h to obtain a uniform glass melt.
[0101] Step 5: Use a casting method to quickly shape the obtained glass melt, put it into an annealing furnace for annealing to eliminate thermal stress. The annealing furnace is set at a temperature of 550° C. and the annealing holding time is 2 hours to obtain boroaluminate microcrystalline glass.
[0102] Step six: Place the boroaluminate glass-ceramics in a high-temperature furnace for crystallization heat treatment. The crystallization temperature is set to 700° C. and the crystallization time is 6 hours. Then, the glass-ceramics with enhanced performance is obtained by cooling the furnace.
[0103] Comparative Example 1
[0104] This comparative example provides a boroaluminate glass-ceramics, and the preparation method thereof is different from that of Example 1 only in that:
[0105] The nano-oxide is mixed evenly with other components of the glass and melted and cast at the same time to obtain a base glass. After the base glass is subjected to a crystallization heat treatment, the obtained microcrystalline glass is translucent and has a visible light transmittance of 53%. By testing the crystal phase size, it is found that the grain size is 60 to 100 nm.
[0106] Comparative Example 2
[0107] This comparative example provides a boroaluminate glass-ceramics, and its preparation method is different from that of Example 2 only in that:
[0108] The nano-oxide is mixed evenly with other components of the glass and melted and cast at the same time to obtain a base glass. After the base glass is subjected to a crystallization heat treatment, the obtained microcrystalline glass is translucent and has a visible light transmittance of 40%. By testing the crystal phase size, it is found that the grain size is 80 to 120 nm.
[0109] Comparative Example 3
[0110] This comparative example provides a boroaluminate glass-ceramics, and its preparation method is different from that of Example 3 only in that:
[0111] The nano-oxide is mixed evenly with other components of the glass and melted and cast at the same time to obtain a base glass. After the base glass is subjected to a crystallization heat treatment, the obtained microcrystalline glass is translucent and has a visible light transmittance of 20%. By testing the crystal phase size, it is found that the grain size is 120 to 150 nm.
[0112] Comparative Example 4
[0113] This comparative example provides a boroaluminate glass-ceramics, and the preparation method thereof differs from that of Example 4 only in that:
[0114] The nano-oxide is mixed evenly with other components of the glass and melted and cast at the same time to obtain a base glass. After the base glass is subjected to a crystallization heat treatment, the obtained microcrystalline glass is translucent and has a visible light transmittance of 53%. By testing the crystal phase size, it is found that the grain size is 60 to 100 nm.
[0115] Comparative Example 5
[0116] This comparative example provides a boroaluminate glass-ceramics, and its preparation method is different from that of Example 5 only in that:
[0117] The nano-oxide is mixed evenly with other components of the glass and melted and cast at the same time to obtain a base glass. After the base glass is subjected to a crystallization heat treatment, the obtained microcrystalline glass is translucent and has a visible light transmittance of 60%. By testing the crystal phase size, it is found that the grain size is 60 to 80 nm.
[0118] Comparative Example 6
[0119] This comparative example provides a boroaluminate glass-ceramics, and its preparation method is different from that of Example 6 only in that:
[0120] The nano-oxide is mixed evenly with other components of the glass and melted and cast at the same time to obtain a base glass. After the base glass is subjected to a crystallization heat treatment, the obtained microcrystalline glass is translucent and has a visible light transmittance of 0%. By testing the crystal phase size, it is found that the grain size is 180 to 200 nm.
[0121] Comparative Example 7
[0122] This comparative example provides a boroaluminate glass-ceramics, and its preparation method is different from that of Example 7 only in that:
[0123] The nano-oxide is mixed evenly with other components of the glass and melted and cast at the same time to obtain a base glass. After the base glass is subjected to a crystallization heat treatment, the obtained microcrystalline glass is translucent and has a visible light transmittance of 39%. By testing the crystal phase size, it is found that the grain size is 80 to 120 nm.
[0124] Comparative Example 8
[0125] This comparative example provides a boroaluminate glass-ceramics, and its preparation method is different from that of Example 8 only in that:
[0126] The nano-oxide is mixed evenly with other components of the glass and melted and cast at the same time to obtain a base glass. After the base glass is subjected to a crystallization heat treatment, the obtained microcrystalline glass is translucent and has a visible light transmittance of 46%. By testing the crystal phase size, it is found that the grain size is 70 to 110 nm.
[0127] In summary, the visible light transmittance of the boroaluminate glass-ceramics of Comparative Examples 1-8 is between 0% and 60%, which is much lower than that of the method of the present invention. By testing the size of the crystal phase, it was found that the grain size was 60 to 200 nm, which greatly limits the transmittance of visible light. The reason is that the traditional addition method of nano-oxide makes it very easy to become a part of the glass melt and the glass network after melting with other glass components. It is difficult to effectively control the precipitation of the crystal phase in the subsequent crystallization process, which makes the precipitated grain size too large, seriously affecting the transmission of visible light and greatly reducing the visible light transmittance of the glass-ceramics.
[0128] Experimental part
[0129] (I) Hardness test
[0130] The present invention tests the hardness of the boroaluminate glass-ceramics prepared in Examples 1 to 8 according to the test method of GB / T 16534-2009 fine ceramic room temperature hardness test method. The test results are shown in Table 1.
[0131] Table 1 Hardness test results
[0132]
[0133] As can be seen from Table 1, the present invention can significantly improve the surface hardness of the basic glass by adding nano oxides of different sizes to the basic glass powder, and can effectively prevent the further expansion of cracks on the glass surface and prevent the glass from cracking in a large area. And by adjusting the size of the added nano oxide, the surface hardness of the glass material can be adjusted, so that the hardness value of the prepared microcrystalline glass is 6.0-9.0GPa.
[0134] (II) Analysis of precipitated phase structure
[0135] The present invention uses SEM (scanning electron microscope) to test the components and sizes of the precipitated phases of boroaluminate glass-ceramics prepared in Examples 1 to 8, respectively, and the test results are shown in Table 2. In addition, before the grain size test, the present invention soaks the fresh glass-ceramics section in a hydrofluoric acid solution with a volume fraction of 3% for 60 seconds to expose the microcrystalline phase.
[0136] Table 2 Analysis results of precipitate phase structure
[0137]
[0138]
[0139] It can be seen from Table 2 that the present invention can adjust the composition and size of the precipitated phase by doping nano-oxides of different sizes and components into the base glass powder, so that the precipitation of the crystalline phase in the microcrystalline glass is controllable, which is beneficial to the controllable precipitation of the nanocrystalline phase in the microcrystalline glass. The size of the crystalline phase precipitated in the microcrystalline glass is 15 to 40 nm, and its absorption and scattering effects on visible light are small, thereby achieving the purpose of strengthening the microcrystalline glass without reducing the visible light transmittance of the base glass.
[0140] (III) Glass visible light transmittance test
[0141] The present invention uses the test method for measuring the light transmittance of daily-use glass in accordance with GB / T 5433-2008 to test the transmittance of the boroaluminate glass-ceramics prepared in Examples 1 to 8 in the visible light band (400-800 nm). The test results are shown in Table 3.
[0142] Table 3 Test results of glass visible light transmittance test
[0143]
[0144] It can be seen from Table 3 that the microcrystalline glass prepared by the method of the present invention has a transmittance of >90% in the visible light band (400-800 nm), and has good application prospects in the field of display cover glass for portable electronic devices.
[0145] In summary, the present invention first prepares a basic glass powder by a molten water quenching method, then externally dopes nanocrystals and mixes them evenly, and finally prepares a microcrystalline glass material by a melt-casting method using the mixed powder, wherein the precipitation control of the crystalline phase in the microcrystalline glass is mainly completed by the precipitation control of the externally doped nanocrystalline phase. In addition, the size, morphology, type, distribution, and content of the externally doped crystalline phase in the present invention can be precisely controlled before glass manufacturing. After being externally doped into the glass and melt-casted with the glass again, the nanocrystalline phase is difficult to be eroded and destroyed by the melt during the second smelting process because the temperature is lower than the first smelting and the smelting time is shorter. The original morphology, size, etc. are completely preserved, and it does not participate in the formation of the basic glass network structure, but remains in the glass as a complete crystalline phase, so it can be used as a precisely controllable nucleation site to control the precipitation of the crystalline phase in the microcrystalline glass, realize the controllable precipitation of the nanocrystalline phase, and complete the efficient preparation of transparent optical microcrystalline glass.
[0146] Obviously, the above embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
Claims
1. A method for preparing boroaluminate glass-ceramics with controllable crystallization, characterized in that: The following steps are involved: S1. According to the following mass percentage ratios, weigh the corresponding raw materials for preparing the basic glass respectively, mix them evenly, and obtain a mixed powder for standby use: Li2O 9%~16%, Al2O3 25%~42%, B2O3 35%~55%, P2O 50%~3%, ZrO2 0~3%, and the total amount of Li2O, Al2O3, B2O3, P2O5 and ZrO2 is 100%; S2, subjecting the mixed powder to a first smelting treatment until it is molten to obtain a glass melt A; rapidly cooling the glass melt A to room temperature, and then grinding it to obtain a basic glass powder; S3, using nano oxide as an induction seed, mixing it with the basic glass powder evenly, and then subjecting it to a second smelting treatment until it is in a molten state, to obtain a glass melt B; S4, casting the glass melt B into a shape by a casting method, and performing annealing treatment to obtain boroaluminate glass-ceramics A; The nano-oxide is one or more of Al2O3, SiO2, ZnO, ZrO2, Y2O3, MgO and CaO; The mass ratio of the nano oxide to the basic glass powder is 1:15-25.
2. The preparation method according to claim 1, characterized in that The method further includes S5, crystallizing the boroaluminate glass-ceramics A at a temperature of 650-750° C. for 2-8 hours to obtain boroaluminate glass-ceramics B.
3. The preparation method according to claim 1, characterized in that: The nano-oxide is added in any state of particles, plates and needles; and the particle size of the nano-oxide is 5-20 nm.
4. The preparation method according to claim 1, characterized in that: In S2, the glass melt A is cooled to room temperature at a cooling rate of 10-60°C / s.
5. The preparation method according to claim 1, characterized in that: The smelting temperature of the first smelting treatment is 1350-1500° C., and the smelting time is 2-8 hours.
6. The preparation method according to claim 1, characterized in that: The smelting temperature of the second smelting treatment is 1100-1350° C., and the smelting time is 0.5-2 h.
7. The preparation method according to claim 1, characterized in that: The annealing temperature of the annealing treatment is 400-600° C., and the annealing time is 2-4 hours.
8. A boroaluminate glass-ceramic obtained by the preparation method described in any one of claims 1 to 7.
9. Use of the boroaluminate glass-ceramics according to claim 8 in preparing display cover glass and transparent optical glass-ceramics for portable electronic devices.
Citation Information
Patent Citations
Boron aluminate microcrystalline glass and preparation method thereof
CN115448600A
A powder, methods for manufacturing and compacting a powder, and bodies produced therefrom
US20160257608A1